2002
DOI: 10.1038/sj.jhh.1001346
|View full text |Cite
|
Sign up to set email alerts
|

The sympathetic nervous system: the muse of primary hypertension

Abstract: the sympathetic neurotransmitter noradrenaline (NA) and postulated that excessive neural tone was a cause of primary hypertension (PH). Thirty years ago, we found raised NA levels in 30-40% of young patients with PH. Laragh found plasma renin activity (PRA) a risk marker for coronary artery disease. With Esler, Miura, and Campese, a close association was found of plasma NA with PRA. We found raised tyrosine hydroxylase activity (AC) in the hearts of a rabbit model of sinoaortic denervated hypertension and in P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
4

Year Published

2004
2004
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 23 publications
1
22
0
4
Order By: Relevance
“…Third, plasma NE concentrations are the result of peripheral sympathetic nerve ending, adrenal medulla secretion and removal mechanisms and therefore allow only for preliminary interpretation when used as an index of systemic SNS activity. 58 To conclude, our data give evidence for an autonomic imbalance in young healthy ss subjects, indicated by a higher HR rise and larger decrease of HRV. The sympathetic hyperactivity and/or stronger withdrawal of parasympathetic tone under the influence of stress may represent a mechanism by which vascular damage occurs in the long run.…”
Section: Cortisolsupporting
confidence: 59%
“…Third, plasma NE concentrations are the result of peripheral sympathetic nerve ending, adrenal medulla secretion and removal mechanisms and therefore allow only for preliminary interpretation when used as an index of systemic SNS activity. 58 To conclude, our data give evidence for an autonomic imbalance in young healthy ss subjects, indicated by a higher HR rise and larger decrease of HRV. The sympathetic hyperactivity and/or stronger withdrawal of parasympathetic tone under the influence of stress may represent a mechanism by which vascular damage occurs in the long run.…”
Section: Cortisolsupporting
confidence: 59%
“…There are numerous studies demonstrating that essential hypertension is accompanied by sympathetic activation. 4,19,20 It has been shown that noradrenaline plays an important role in the regulation of blood pressure, and the increased plasma catecholamine levels have been observed in the development of hypertension. As the rate-limiting enzyme in catecholamine biosynthesis, the TH gene is considered as a logic candidate for the etiology of hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to the biological process of blood pressure regulation, we focused on 11 candidate genes associated with: (1) renin-angiotensin-aldosterone system (RAAS), including ACE, angiotensin II receptor type I (AGTR1), and aldosterone synthase (CYP11B2) 15,18 ; (2) sympathetic nervous system, including ␣-1 adrenergic receptor 1A (ADRA1A), ␤-2 adrenergic receptor (ADRB2), and tyrosine hydroxylase (TH) 4,19,20 ; (3) lipoprotein metabolism, including lipoprotein lipase (LPL) 21 ; (4) intracellular messengers, including G protein ␤ polypeptide 3 (GNB3) and epithelium nitric oxide synthase (NOS3) 22,23 ; and (5) sodium and electrolyte balance, including G protein-coupled receptor kinase 4 (GRK4) and protein kinase lysine-deficient 4 (WNK4) 24,25 (as shown in Table 1). …”
mentioning
confidence: 99%
“…6,7 Increased peripheral sympathetic activity is suggested to play a key role especially in the early phases of hypertension in young subjects. 3,8 Furthermore, as reviewed by DeQuattro and Feng, 9 several research groups found increased norepinephrine levels in cerebrospinal fluid and increased norepinephrine turnover in hypothalamic centres of hypertensive (HT) subjects. Central catecholaminergic pathways transmit neural stimuli to neuroendocrine hypothalamic centres that regulate endocrine activity of pituitary cells.…”
Section: Introductionmentioning
confidence: 99%